Ankle-Brachial Index: Nurses Strategy To Cardiovascular Disease Risk Factors Identification - Maggi,Daniela Luisa (2014)
Elevated risk of fatal and non-fatal cardiovascular events is associated with high prevalence of peripheral arterial disease, with assessment through the ankle-brachial index (ABI). This study aimed to demonstrate that the ABI and the Edinburgh Claudication Questionnaire are tools to be used by nurses in prevention and/or treatment of CVD (cardiovascular disease). A cross-sectional study was carried out with patients from a cardiovascular clinic. The Edinburgh Claudication Questionnaire was applied and the ABI was measured with the formula (ABI= Blood Pressure Ankle/Blood Pressure Brachial). A total of 115 patients were included, most were females (57.4%), aged 60.6 ± 12.5 years. The most prevalent risk factors were hypertension (64.3%), physical inactivity (48.7%) and family history (58.3%). The study showed that abnormal ABI was frequently found and 42.6% of the patients with abnormal ABI showed intermittent claudication. The method to evaluate the ABI associated to the Edinburg Claudication Questionnaire, can be easily used by nurses in the clinical evaluation of asymptomatic and symptomatic CVD patients.